IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) DALAM MENINGKATKAN MUTU LULUSAN DI SMK MINHAJUTH THULLAB AL-AMIN KABUPATEN MESUJI LAMPUNG - Anwar, Miftahul (UNISAN JURNAL, 2025)
Examining the dynamics of educational management in madrasas which blend traditional values with the demands of modernization in the age of globalization is the goal of this study. As educational establishments founded on the Islamic faith, madrasas must balance upholding religious customs with providing instruction that is pertinent to contemporary trends. Using a descriptive-qualitative methodology, this study examines a number of works pertaining to Madrasa Education Management: Between Tradition and Modernization. The study's findings demonstrate that while madrasa education management continues to uphold traditional values, such as a rigorous curriculum based on religion, it is also beginning to incorporate contemporary elements, such as the use of technology in the classroom, more open financial management, and professional training to improve the caliber of human resources. Aligning the two presents difficulties, though, particularly when it comes to infrastructure and the value of innovation. According to the study's findings, madrasas must create a management model that can support both maintaining customs and implementing contemporary methods that are consistent with world events without sacrificing their Islamic identity in order to meet the best educational objectives.